The Berenstain bears and the sitter - Berenstain, Stan, 1923-2005 (Berenstain, Stan, 1923-2005. First time books., 1981)
Brother and Sister Bear are not happy with the idea of Mrs. Grizzle for a baby-sitter, but they find her drawstring bag very intriguing.